ТЕОРЕТИЧНІ АСПЕКТИ БЮДЖЕТНОЇ ДЕЦЕНТРАЛІЗАЦІЇ В КОНТЕКСТІ РЕФОРМ ДЕРЖАВНОГО УПРАВЛІННЯ В УКРАЇНИ (Світ фінансів, 2018)
Бондарук Т. Г., Вінницька О. А.,  Дубина М. В. Теоретичні аспекти бюджетної децентралізації в контексті реформ державного управління в Україні. Обґрунтовано, що бюджетна та фінансова децентралізація значним чином впливатиме на формування місцевих бюджетів. Встановлено, що курс на децентралізацію окреслює як перспективи, так і проблеми розвитку України. Здійснено групування основних переваг і позитивних наслідків децентралізації. Встановлено, що децентралізація може мати також ризики й небезпеки, групування яких здійснено в статті. Бондарук Т. Г., Винницкая О. А.,  Дубина М. В. Теоретические аспекты бюджетной децентрализации в контексте реформ государственного управления в Украине.Обосновано, что бюджетная и финансовая децентрализация значительным образом влияет на формирование местных бюджетов. Установлено, что курс на децентрализацию определяет как перспективы, так и проблемы развития Украины. Сгруппированы основные преимущества и положительные последствия децентрализации. Установлено, что децентрализация может иметь также риски и опасности, группирование которых осуществлено в статье. Bondaruk T., Vinnytska O.,  Dubyna M. Theoretical aspects of budget decentralization in the context of public administration reforms in Ukraine.Introduction.The urgency of studying theoretical foundations of budget decentralization for Ukraine is conditioned by the necessity of developing an effective scheme of macroeconomic regulation of social and economic processes in the context of decentralization. The process of social and economic development in Ukraine on a democratic and legal basis is impossible without increasing the role of the local self-government. Decentralization is one of the main motive forces in reforming self-government today.The purposeis deepening theoretical and methodological principles of budget decentralization and theoretical aspects of budget decentralization with the definition of its influence on processes of state regulation in Ukraine.Results.It is substantiated that in modern science theoretical aspects of decentralization are considered in relation to its types. The classification of decentralization types is carried out depending on their characteristics: financial (fiscal) one is the process of distribution of functions, financial resources and responsibility for their use between central and local levels of management; budget one, in the broadest sense, is the division of responsibility between authorities of different levels (including national governments, regional authorities and local self-government bodies) with the management of budgetary resources; in the narrow sense it is the presence of certain functions and powers at the local level, autonomy of local authorities in making independent decisions in the fiscal sphere.Conclusions.It is substantiated that budget and financial decentralization considerably influences the formation of local budgets. It is found that the decentralization course shows both prospects and problems of the Ukrainian development. Grouping the main benefits and positive effects of decentralization is carried out. The research analysis made it possible to establish that decentralization may have the risks and dangers grouped in the article.